Once & future. Volume four, Monarchies in the U.K. - Gillen, Kieron (BOOM! Studios, 2022)
"Bridgette, Duncan, and Rose, -- along with the entirety of Britain -- are dragged into the Otherworld. It's a land of predatory monsters and things seem like they can't get any worse. Of course they can. A rival king rises to confront Arthur, plunging the land into civil war... and both pursue Bridgette, Duncan and Rose as they travel across the land, desperately trying to find a way to return Britain to its senses--